Fake News and Democracy in Latin America (2022)
Diverse territories of Latin America are immersed in important situations to-day. The region is not only facing shortages, inequities, and inequalities a large part of the population has to live with, but also constant information, disin-formation and fake news that permeate their minds and erode their freedom of decision and action in democratic processes. The scenario they are going through calls for a deep shake from its foundations, given the discourse of knowledge beyond a robust wave of information, coming from unusual sourc-es, some of them disrupting the effort to ascertain the truth of the facts and being apparently at the service of economic and/or political hegemonies. This text proposes a comprehensive approach to fake news and the scope of influ-ence they have on individual freedom with repercussions on the weak Latin American democracy.